Effect of students’ attitude on environmental factors and green practice (Reduce, Recycle & Reuse) / Musramaini Mustapha … [et al.] - Mustapha, Musramaini; Asmui, Mas'udah; Syed Wahid, Sharifah Norhuda; Mohd Zaki, Suhanom; Razali, Saifudin (Faculty of Accountancy, 2019)
Going green must derive from green practice. The green practice involves 3R process that focus on effort to reduce, recycle, and reuse. The recycle issue always became on top in the list, indirectly other effort reduce and reuse also important toward environmental concerns. Thus, the researchers found it vital to conduct a study on the green practice process related to 3R (reduce, recycle, and reuse) based on affective and cognitive environmental, also interested to assess the role of students’ attitude as a mediator in the relationship between the variables of interest. For that reason, 112 respondents were selected to participate and all of them completed set of questionnaires. The findings show that, only affective environmental and students’ attitude have a significant and positive influence towards 3R processes. In addition, students’ attitude does not mediate the relationship between affective environmental and 3R since the indirect effect is smaller than direct effect. This finding determine Universiti Teknologi MARA students are putting their efforts and support toward environmental concern. Thus, business industry and tertiary institutional may need to collaborate to start encouraging their customers move effort toward 3R process to support green practice.